Tissue Doppler echocardiography predicts long-term cardiovascular mortality: the Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) legacy 20-year follow-up study - Simon Thom; Alice Stanton; Jamil Mayet; Amit Kaura; Darrel Francis; Anoop SV Shah; Andrew Sharp; Alun D Hughes; Neil R Poulter; Anenta Ratneswaren; Tong Wu; Somayeh Rostamian; et al. (Open Heart)
Background Left ventricular diastolic function as assessed by tissue Doppler echocardiography predicts cardiovascular event rates at 4 years of follow-up in patients with hypertension. Our aim was to evaluate whether this extends to predicting cardiovascular mortality after 20 years of follow-up.Methods Conventional (E) and tissue Doppler (e′) echocardiography was performed on hypertensive participants in the Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) with long-term follow-up ascertained via linkage to the Office of National Statistics. Cardiovascular mortality was defined as death from coronary heart disease, stroke and other cardiovascular aetiology such as heart failure or peripheral vascular disease. Unadjusted and adjusted Cox regression survival models were constructed to investigate the association between tissue Doppler echocardiography measurements and long-term cardiovascular mortality.Results Among 506 hypertensive patients (median age 64, interquartile range (58, 69), 87% male), there were 200 (40%) deaths over a 20-year follow-up period. 60 deaths (12%) were cardiovascular-related.A reduction in e′ was independently associated with increased cardiovascular mortality, after adjusting for the ACC/AHA Atherosclerotic Cardiovascular Disease (ASCVD) risk score, with an inverse HR of 1.22 per 1 cm/s decrease (95% CI 1.04–1.43). A higher E/e′ ratio was independently associated with increased cardiovascular mortality, after adjusting for the ASCVD risk score, with an HR of 1.12 per 1-unit increase (95% CI, 1.02 to 1.23).Conclusions Impaired left ventricular diastolic function, measured using tissue Doppler echocardiography through e′ and E/e′, independently predicts increased cardiovascular mortality over 20 years in hypertensive patients, highlighting its long-term prognostic significance.